ARİSTOTELES'İN DOĞA -FİZİK- FELSEFESÎ - Hüseyin Gazi Topdemîr (Felsefe Dünyası)
The aim of this paper is to discuss Aristotle's representation of nature and the universe based on his philosophy of nature as explained in Physics, On the Heavens, On Generation and Corruption and the Meteorology. These works contain a collection of detailed observations on nature. The Meteorology contains a similar collection on natural phenomena such as rain, clouds and the formation of rainbows. The others try to explain these observations in the light of the explanatory scheme defended by Aristotle in his more theoretical reflections on nature. These reflections especially those in Physics and Generation and Corruption aim to develop a full account of nature, form, matter, cause and change that reflect Aristotle's views on natural phenomena. His natural philosophy and cosmology are brought together in On the Heavens